ANALISIS PERBEDAAN KOMITMEN PROFESIONAL DAN SOSIALISASI ANTISIPATIF MAHASISWA BIDIKMISI DAN NON-BIDIKMISI PADA HUBUNGANNYA DENGAN WHISTLEBLOWING - Yusra, Muhammad; Yunita, Nur Afni; Nurhasanah, Nurhasanah (Jurnal Akuntansi dan Keuangan, 2021)
This study aims to look at the effect of professional commitment and anticipatory socialization of bidikmisi and non-bidikmisi accounting students at Malikussaleh University on its relationship with whistleblowing. In addition, this study also aims to see differences in the level of professional commitment and anticipatory socialization between students of Bidikmisi and non-Bidikmisi Accounting at Malikussaleh University. Sampling in this study using the Slovin formula is a sampling technique that uses a critical value or accuracy limit of 0.1, so that the sample obtained in this study amounted to 90 respondents from a total population of 286 students. This study uses multiple regression analysis techniques with hypothesis testing using the SPSS 22 program. The results show that professional commitment and anticipatory socialization affect whistleblowing, as well as differences in the level of professional commitment and anticipatory socialization between bidikmisi and non-bidikmisi students at Malikussaleh University